Android-based augmented reality in science learning for junior high schools: Preliminary study - Triana Rejekiningsih; Iwan Maulana; Mochamad Kamil Budiarto; Taufiq Subhanul Qodr (Institute of Advanced Engineering and Science, 2023)
Technology in education encourages more effective learning facilitation processes. The lack of variation and innovation in the use of technology used in the form of learning media as a means of supporting learning activities raises many new problems for educational institutions. This research aims to identify the need to create innovations in the implementation of science learning, whose research focus is to analyze the needs for developing smartphone-based innovative augmented reality (AR) learning media. This research is descriptive qualitative. Data collection techniques are observation, interviews, and questionnaires. Teachers and students of junior high schools in Surakarta became the subject of this research. The results showed that students were less focused and unmotivated when participating in the learning process. In addition, the use of learning media is still conventional and not interactive, even though currently all students have smartphones. Based on field facts, the media used by teachers still tends to be conventional, and the majority of students have technological devices such as smartphones, there is great potential for developing innovative technology-based learning media. Smartphone ownership and the lack of interactive learning media are important foundations in innovating the development of smartphone-based augmented reality.